WE5.12 Stress During Laparoscopic Appendicectomy: A Study into the Measurement of Surgeon's Heart Rate During The Critical Steps of A Laparoscopic Appendicectomy. (9th August 2022) - Kersey, James; Clements, Caterina; Bezzaa, Sabrina; Jamal, Karim; Nehra, Dhiren; Lewis, Trystan
Abstract: Aims: Heart rate variability (HRV) is a validated marker of physiological stress, a lower HRV indicating increased stress. We aim to evaluate the HRV of an on call surgical registrar during a laparoscopic appendicectomy to determine which step of an operation is most stressful and any attributing factors to trainee stress. Methods: An observational study was performed using a commercially available chest strap to measure HRV. HRV was recorded on different surgical registrars performing laparoscopic appendicectomy at a DGH. HRV was analysed during four critical steps: insertion of ports, dissection of mesoappendix, endoloop placement and ligation of appendix. Impact of registrar grade and consultant presence were also evaluated. Results: 15 recordings from seven different registrar's (ST3 – ST8) were obtained. Average heart rate was 74–130bpm. HRV was observed to be less during port insertion (9.22) and mesoappendix dissection (8.42) compared to the rest of the operation (9.86) indicating a higher level of stress. Ligation of the appendix showed an increased HRV indicating less stress (9.34). A significant difference was observed between ST3/4 and ST5+ grade for mesoappendix dissection (7.39 and 9.46 respectively), the step associated with most stress (p<0.05 using paired T-test) Conclusions: HRV is highest during mesoappendix dissection compared to that of the whole operation. HRV increases after this step showing that trainees experience increased stress up to and including this step of the operation. The ST3/4 group showed a significantly lower HRV during this step compared to the ST5+ group. Consultant presence did not significantly affect HRV.